An overview of FDA-approved biologics medicines. Issue 4 (April 2015) - Kinch, Michael S.
Highlights Biologics approvals grew from the early 1980s through 2010, stabilizing thereafter. Three different disease categories capture more than 70% of initial antibody approvals. The relative number of biologics (to small molecules) might be declining.